BIBLIOMETRIC ANALYSIS OF ACUPUNCTURE RESEARCH FRONTS AND THEIR WORLDWIDE DISTRIBUTION OVER THREE DECADES - Fu, Jun-Ying; Zhang, Xu; Zhao, Yun-Hua; Tong, He-Feng; Chen, Dar-Zen; Huang, Mu-Hsuan (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Considerable research has been conducted on acupuncture worldwide. This study chronologically examined the changing features and research fronts of acupuncture and elucidated the differences among the six most productive countries. Methods: Bibliographic coupling is a powerful tool for identifying the research fronts of a field. Acupuncture-related publications worldwide and from the six most productive countries during 1983–2012 were retrieved from the Science Citation Index Expanded and Social Science Citation Index. To form the research fronts, the 100 most highly cited papers (HCPs) were clustered in terms of references shared. Results: The United States had the highest proportion of HCPs. The effectiveness of acupuncture in areas such as relieving neck and back pain, migraines and headaches, and knee osteoarthritis symptoms was a predominant topic. Initially, the endogenous opioid peptide system was the primary research focus in the acupuncture mechanism research; however, during 1993–2012, researchers focused more on the functional magnetic resonance imaging of brain activity. In addition, acupuncture use and prevalence, the attitudes of health practitioners, and the effects of expectancy and belief were also major topics. Researches from Western countries, including the United States, England, and Germany, showed more interest in clinical trials and economic- and ethics-related studies, whereas those from East Asian countries including China, Japan, and South Korea focused more on mechanism research. Conclusion: Western countries dominated the research fronts of acupuncture. The patterns of the research fronts varied worldwide, indicating continuity and innovation in research in each country.